DIRECTIONS OF FOOD WASTE PROCESSING DEVELOPMENT IN THE CONTEXT OF THE FORMATION OF A CIRCULAR ECONOMY - GOTSII, Bogdan; TULCHINSKIY, Rostislav; POHREBNIAK, Anna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article substantiates the directions of food waste processing development in the context of the formation of a circular economy, which involves the reuse of materials, extension of the economic chain of resource use, waste avoidance and recycling. The relevance of the study is due to the fact that among the main problems in the field of waste management remain a significant negative impact on the environment and insufficient use of the potential of food waste as an available raw material for creating value-added products in the context of the formation of a circular economy. It is proven that rational food waste management is becoming a necessary condition for the sustainable development of enterprises and requires an integrated approach to creating an effective food waste management system, as well as the development of state programs and policies in the context of implementing the principles of the circular economy. It is substantiated that the processing of food waste and its transformation into value-added products is an important component of the development of modern food enterprises within the framework of the concept of a circular economy. The forms of food waste processing, including composting and biogas production, are analyzed. Composting is an effective means of transforming food waste into a valuable product and includes the following stages: waste collection, compost pile formation, air exchange and humidity provision, decomposition process, finished product. In conditions of electricity shortage and limited traditional energy resources, biogas technologies can become a powerful factor in the development of the national energy sector in the context of the formation of a circular economy. The process of biogas production from food waste includes the following stages: raw material collection, raw material pre-treatment, anaerobic digestion, biogas collection and purification. The activities of Ukrainian enterprises that are leaders in the biogas sector of the country are analyzed. It is established that food waste processing plays a key role in the development of a circular economy based on the rational use of resources and reducing the environmental load.
Keywords: circular economy; waste management; food waste processing; biogas production; composting